Pengembangan Lembar Kerja Peserta Didik Elektronik (E-LKPD) Berbasis Higher Order Thinking Skill (HOTS) Materi Magnet - Pamungkas, Nurkhalimah Ery; Fitriyani, Fitriyani (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
This study aims to develop HOTS-based Electronic Student Worksheets, to find out the assessments of three experts and the opinions of educators and students in grade VI SD. This study uses a type of learning design development research or R&D using the ADDIE model. The research subjects consisted of three experts (media experts, linguists, material experts) and students of class VI SD. The instrument used in the form of a questionnaire given to three experts was obtained from the research results, namely qualitative data which were analyzed using quantitative data in the form of numerical data. The results of this study, produced HOTS-based E-LKPD products that met very good criteria with an average validation score of three validators obtained a value of 96.9% with a very feasible category to use, and a practicality level of 87.9% was on very practical criteria and the level of effectiveness with an average of 90% is in the very effective category. HOTS-based E-LKPD teaching materials are appropriate, practical and effective for use in learning.